Korean Cyberfeminism: emergence, characteristics and results - Bavoleo, Bárbara Inés (2020)
The massification and widespread of the available tools on Internet contributes to give shape and movement to the contemporary social and political life. The variety of information and communication possibilities converges in the formation of groups and movements with shared interests and identities. In this context, in the Republic of Korea, feminist groups have emerged and proliferated promoting their demands in a quickly, anonymous and simultaneous way and were nourished by the wide possibilities offered by the cyberspace. The objective of this paper is to analyze the circumstances that motivated the conformation of these feminist groups on the web, defined under the conceptual framework of cyberfeminism, its characteristics and the consequences of its actions at a cultural and political level. This information allows us to outline the possibilities of its future development. The analysis dimensions include: the member’s characteristics, the collaboration’s types, the topics of interest, the action’s modalities, and the positioning with respect to the LGBT community.